(untitled) (Palíndromo, 2019)
Atelier is an intrinsic visual arts concept development most sens what aproachs office, workshop, studio and laboratory. The differences among concepts for atelier indicates economical and epistemological variations. With Michel Foucault ethics treat the importance of these spaces being a heterotopic place.